An Analysis of Flouting Maxims in “Sonic the Hedgehog 2” Movie: Pragmatics Approach - Melania, Putri; Mubarak, Zia Hisni (eScience Humanity Journal, 2023)
This qualitative research studied the types of flouting maxims that appeared in Sonic the Hedgehog 2 movie. The initial idea of the research comes from the fact that movie often represents linguistic phenomenon including flouting maxims that is done with purpose or intention. In studying this phenomenon, this research approached the data source using Pragmatics and applies Grice’s theory of flouting maxim to help explaining the phenomenon. This article collects the relevant utterances using non-participation observation and analyzes them by using Pragmatic Identity Method (Sudaryanto, 2015). The research identified 15 utterances where 7 of them are flouting maxim of relation, 4 of them are flouting maxim of manner, 2 of them are flouting maxim of quality, and 2 of them are flouting maxim of quantity. Most of the flouting maxims are done for the purpose of warning, emphasizing, or letting the other know that their statement is ridiculous.